Safety and Efficacy of Balloon Remodeling Technique during Endovascular Treatment of Intracranial Aneurysms: Critical Review of the Literature - Pierot, L.; Cognard, C.; Spelle, L.; Moret, J. (American Journal of Neuroradiology, 2012)
SUMMARY: The balloon remodeling technique was initially designed for the endovascular treatment of anatomically complex aneurysms, specifically wide-neck aneurysms. A nondetachable balloon is inflated in front of the aneurysm neck during coil deposition and removed at the end of the procedure. Some controversies regarding the safety of the technique were introduced by the recent publication of a series showing a much higher rate of complications with the remodeling technique compared with the standard coiling technique. However, recent data from the literature review and from the large ATENA and CLARITY series show that the safety of standard coiling and remodeling is quite similar. Anatomic results are also probably better after remodeling. Finally, due to equivalent safety and better anatomic results, the remodeling technique can be widely used in the management of both ruptured and unruptured aneurysms. ATENAAneurysms Treated by Endovascular ApproachCLARITYclinical and anatomic results in the treatment of ruptured intracranial aneurysmsCHUCentre Hospitalier UniversitaireEVTendovascular treatment